Grassland improvement in subtropical Guangdong Province, China - Tarawali, Shirley A. (1995)
Chamaecrista rotundifolia cWynn has been identified as a promising forage legume for use in subhumid Nigeria. To establish if other accessions of this species have potential in the region, 21 accessions were evaluated for flowering, seed production, dry matter production, disease and pest incidence and drought tolerance. A number of later flowering accessions gave higher dry matter yields than cWynn, although some (ILCA 15603 and 15604) showed susceptibility to anthracnose disease. One of the most promising accessions is ILCA 14167 which warrants further testing of nutritional qualities, palatability and potential in a pasture situation.